IMPLEMENTASI KEBIJAKAN DAN EFEKTIVITAS PENGELOLAAN TERHADAP PENERIMAAN RETRIBUSI DI PASAR LANCIRANG KECAMATAN PITU RIAWA KABUPATEN SIDENRENG RAPPANG - Ahmad Mustanir; Jusman Jusman (AkMen JURNAL ILMIAH, 2016)
This study aims to know about levies market policies towards improving reception on the Lancirang Market of Pitu Riawa in Sidenreng Rappang Regency and to determine market levies managementby the Department of Revenue to the increased acceptance of market levies in Lancirang Market in Sidenreng Rappang.The method used in this research is quantitative research method (table percentage).Techniques of data collection is by distributing questionnaires to the respondents amounted to 81 people for a compulsory levy and 12 people from the Department of Revenue employee and conducting the direct interviewto informants of 5 people. From this research, it can be presented that the factors which influence the policy implementation of Regional Regulation Nu. 13 of 2011 about Service Fees Market Nu 4, includes communicating, organizing, implementing, and monitoring the obtained 78% based on the accumulated number of overall average percentage of indicator of market retribution management. In this research, there arethe indicators of market retribution management in Lancirang market which include planning, organizing, implementing, and monitoring of the obtained 67.25% based on the accumulated number of overall average percentage of the indicators of market retribution management. As the indicators of acceptability Regional Income from market levy sector Nu 5, covers expanding the revenue base, strengthening the process of collection, improving the supervision, increasing the administrative efficiencyand reducing the cost of collection, and improving the capacity through better planning, which of the 12 respondents who participated obtained 75 , 4% of the accumulation of each indicator output or outcome of research undertaken.